Eye movement desensitization and reprocessing (EMDR) in patients with a personality disorder. Issue 1 (31st December 2020) - Hafkemeijer, Laurian; de Jongh, Ad; van der Palen, Job; Starrenburg, Annemieke
ABSTRACT: Background: Little is known about the effects of targeting memories of adverse (childhood) events in people with a personality disorder (PD). Objective : Determining the effectiveness of brief EMDR therapy in individuals with PD. Method: In a randomized-controlled trial, 97 outpatients with a PD as main diagnosis were allocated to either five (90 minutes) sessions of EMDR therapy ( n  = 51) or a waiting list (WL) control condition ( n  = 46) followed by 3 months of treatment as usual for their PD. Individuals with posttraumatic stress disorder (PTSD) were excluded. Measurements were performed on psychological symptoms, psychological distress, and personality dysfunctioning. Outcomes were compared at baseline, post-treatment, and at 3-month follow up. Data were analysed as intent-to-treat with linear mixed models. Results: EMDR therapy yielded significant improvements with medium to large effect sizes for the primary outcomes after treatment, i.e. psychological symptoms (EMDR: d =.42; control group: d =.07), psychological distress (EMDR: d =.69; control group: d =.29), and personality functioning (EMDR: d =.41; control group: d = −.10) within groups. At 3-month follow-up, after 3 months of TAU, improvements were maintained. Significant differences were found between both groups regarding all outcome measures in favour of the EMDR group at post-treatment (ds between −.62 and −.65), and at follow-up, after 3 months of TAU (ds between −.45 and −.53). Conclusions: The results suggest that EMDR therapy can be beneficial in the treatment of patients with PDs. More rigorous outcome research examining long-term effects and using a longer treatment track is warranted. Abstract : HIGHLIGHTS: The results of this study show that a brief intensive trauma-focused treatment (EMDR) can be beneficial for individuals with personality disorders to reduce psychological symptoms and to improve their functioning.